2020
DOI: 10.1016/j.fct.2020.111639
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the safety assessment of medicines currently used in the COVID-19 disease treatment

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 63 publications
0
31
0
1
Order By: Relevance
“…Adverse effects are common with remdesivir, but few studies exist that focus on remdesivir and its effects on the cardiovascular system [1,2,9,10,12,13]. Out of a study of 53 patients receiving remdesivir, 32 patients (60%) experienced adverse events during follow-up [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse effects are common with remdesivir, but few studies exist that focus on remdesivir and its effects on the cardiovascular system [1,2,9,10,12,13]. Out of a study of 53 patients receiving remdesivir, 32 patients (60%) experienced adverse events during follow-up [5].…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse effects of remdesivir are increased hepatic enzymes, diarrhea, anemia, rash, renal impairment, and hypotension [1,2,8,9]. Elevated alanine aminotransferase (ALT) and aspartate aminotransferase (AST) have been shown to be reversible after discontinuation of remdesivir per studies [8][9][10]. The purpose of our case reports is to highlight two cases who developed adverse drug reactions (ADRs), both with bradycardia, and one with QTc prolongation with T-wave abnormality during remdesivir treatment, which resolved following early discontinuation of the therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the comorbidities in COVID-19 patients, the health status of these individuals is complex. Therefore, the medication’s adverse effects and their combinations in treatment plans should be given special attention [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a latest research has demonstrated that hydroxychloroquine or chloroquine used alone or with a macrolide, do not show a benefit on in-hospital outcomes for COVID-19 and on the contrary, were relevant to decrease in-hospital survival as well as increase frequency of ventricular arrhythmias ( Mehra et al, 2020 ). Therefore, a comprehensive evaluation of the safety profile of potential therapeutic agents against COVID-19 is of paramount importance ( Javorac et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%